Management of Adnexal Mass During Cesarean Section - Gurung, Monica; Baral, Gehanath (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To find out the prevalence of adnexal mass during Cesarean Section, its management and histological profile. Methods: This is a retrospective study conducted for 4 years from 2013 to 2017 at Paropakar Maternity and Women’s Hospital, Kathmandu, Nepal. There were 18993 Cesarean Sections out of 72263 total births screened for adnexal masses from operation theatre register and record section. Results: The incidence of adnexal mass during cesarean section was 0.31% (58 out of 18993). Among them 15.52 % diagnosed antenatally and 84.48 % were incidentally diagnosed during cesarean section. Among 58 cases, 6 (10%) were bilateral amounting to 64 adnexal masses among which 35 (54.69%) masses had cystectomy, 20 (31.25%) masses had oophorectomy, 6 (9.37%) had aspiration/ drilling done and 3(4.69 %) masses were left without intervention. Among those cases only 48 histopathological reports were available. All the masses were benign and the most common was benign mature cystic teratoma (34; 69.38 %) and the least common was fibroma (1; 2.04%). Conclusions: Adnexal masses during cesarean section should undergo surgical removal.